Impact of temperature on the Narcotrend Index during hypothermic cardiopulmonary bypass in children with sevoflurane anesthesia. (May 2018) - Dennhardt, Nils; Beck, Christiane; Boethig, Dietmar; Heiderich, Sebastian; Horke, Alexander; Tiedge, Sebastian; Boehne, Martin; Sümpelmann, Robert
Background: During cardiopulmonary bypass (CPB) in children, anesthesia maintained by sevoflurane administered via the oxygenator is increasingly common. Anesthetic uptake and requirement may be influenced by the non-physiological conditions during hypothermic CPB. Narcotrend-processed EEG monitoring may, therefore, be useful to guide the administration of sevoflurane during this phase. Objective: The objective of this prospective, clinical, observational study was to assess the correlation between body temperature, Narcotrend Index (NI) and administered sevoflurane in children during CPB. Methods: Forty-four children aged 0 to 10 years undergoing hypothermic cardiac surgery were studied. On bypass, anesthesia was maintained with sevoflurane administered via the oxygenator of the heart-lung machine. Nasopharyngeal temperature, NI and minimum alveolar concentration (MAC) of sevoflurane were recorded in intervals of 10 minutes. Expiratory gas was sampled from the oxygenator's sole expiratory port via a separate connecting line and the MAC was measured by the agent analyzer of the anesthesia machine. Results: Raw (r = 0.74) and corrected (r = 0.73) r-values show that narcosis depth (as indicated by NI) can primarily be explained by the interaction of MAC and temperature. The analysis of variance (without the interaction term) confirms the significant and independent association of both factors, MAC (p<0.004, 95%CI: 0.19 to 0.46) and temperature (p<0.0001, 95%CI: 0.68 to 0.78), with the NI. During hypothermia, sevoflurane had been reduced significantly (r = 0.41, p<0.0001, 95%CI: 0.33 to 0.48). Conclusion: Perfusionists and anesthetists should be aware of the results of processed electroencephalograph (EEG) monitoring during CPB. Sevoflurane requirements differ inter-individually; they may decrease during cooling and increase during rewarming. Therefore, it seems reasonable to include the results of processed EEG monitoring when administering sevoflurane during CPB in children, but further studies are necessary to confirm this thesis.